Reconciliation and Fulfillment of Civil Rights: Case of Ahmadiyya Adherents in Manislor, Kuningan, West Java - Sodik, Mochamad; Sujibto, B. J.; Gufron, Gufron (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2023)
Religious conflicts pose a threat to social integration, including those involving the Ahmadiyya Muslim community in Indonesia. This article discusses the post-conflict reconciliation and fulfillment of civil rights among Ahmadiyya adherents in Manislor, Kuningan, West Java, Indonesia. Social actors have a powerful position in the reconciliation and fulfillment of civil rights, which have become one of their most apparent violations against Ahmadiyya adherents in Manislor. This study uses a qualitative approach with data collected through fieldwork and ethnographic observations with Ahmadiyya adherents in Manislor. This article scrutinizes 1) the typologies of post-conflict reconciliation, 2) reconciliation efforts in the communities by leveraging cultural and religious aspects, and 3) the struggles of fulfilling civil rights, such as issuing marriage certificates and identification cards. The results show that the willingness of Ahmadiyya elites to meet with stakeholders and socio-religious organizations, particularly in Kuningan regency, created a space for a dialogue of understanding that helped the reconciliation between Ahmadiyya and the wider community in Manislor. This study contributes to clarifying the pattern of reconciliation based on the local approaches durably practiced by Ahmadiyya adherents in Manislor, Kuningan, West Java.